AB1216-HPR A Study of Possible Correlations of Sleep Disturbance with Disease Activity, Psychological State and Health Status in Patients with Rheumatoid Arthritis. (9th June 2015) - Yukioka, C.; Nakahara, H.; Fusama, M.; Yukioka, K.; Kuroiwa, T.; Yukioka, T.; Inoue, M.; Nakanishi, T.; Takai, N.; Higashi, K.; Miura, Y.; Murata, N.; et al.
Abstract : Background: Sleep disturbance occasionally occurs in patients with rheumatoid arthritis (RA). It is not clear which factor mostly influences sleep disturbance in patients with RA. Objectives: We evaluated which factors are correlated with sleep disturbance in patients with RA. Methods: Patients with RA who met the 1987 revised criteria of ACR for RA or the 2010 ACR/EULAR classification criteria for RA were selected for this study. The levels of disease activity of RA was evaluated using swollen joint count (SJC), tender joint count (TJC), evaluator global assessment (EGA) and patient global assessment (PGA). Sleep disturbance was evaluated utilizing the Pittsburgh Sleep Quality Index (PSQI). Psychological factors were examined utilizing the Center for Epidemiological Studies Depression Scale (CES-D), the Hospital Anxiety and Depression Scale-Anxiety-Depression (HADS-D) and Anxiety (HADS-A) and the State-Trait Anxiety Inventory (STAI). Health status was evaluated with Short Form-36 (SF-36). We assessed the correlation of sleep disturbance with disease activity, psychological factors and health status. Data analyses were performed using Spearman correlation analysis. Results: 112 patients with RA were recruited. Average of age: 54.8 years old, disease duration: 11.4 years, SJC: 2.7, TJC: 2.2, PGA: 23.2mm, EGA: 16.2mm. PSQI was not correlated with age, duration, SJC, TJC and EGA, while it was weakly statistically correlated with PGA (r=0.2592, p=0.0058). With regard to psychological state, PSQI was significantly correlated with CES-D (r=0.5165, p<0.0001), HADS-A (r=0.4139, p<0.0001), HADS-D (r=0.4182, p<0.0001), STAI (State) (r=0.476, p<0.0001), while there was no statistically significant difference between PSQI and STAI (Trait). With regards to health status, physical summary score (PCS) of SF-36 was not correlated with PSQI statistically, while mental summary score (MCS) was significantly correlated with PSQI (r=0.4186, p<0.0001). Conclusions: Sleep disturbance was more strongly correlated with psychological state rather than disease activity and physical state. Psychological state is correlated with PGA [1] and PGA is reported to be a limiting factor for reaching remission of RA [2]. Addressing sleep disturbance symptoms may improve not only psychological state but also PGA, resulting in achievement of remission. References: Fusama M, et al. Mod Rheumatol in press. Studenic P, et al. Ann Rheum Dis 2012; 71: 1702-5. Disclosure of Interest: None declared